Psychiatric Co-morbidity with Obsessive Compulsive Disorder - Das, Anupam; Malakar, Choity (KYAMC Journal, 2024)
Background: Obsessive-compulsive disorder is a chronic psychiatric disorder. It is associated with substantial psychiatric comorbidity. Major Depressive disorder & mixed anxiety and depressive disorder are the most common psychiatric co-morbidities. Objective: To evaluate the psychiatric co-morbidity with obsessive-compulsive disorder. Materials and Methods: It was a descriptive and cross-sectional clinical study. It was conducted in the Outpatient Department of Psychiatry, Khwaja Yunus Ali Medical College, Sirajganj from January 2021 to December 2022. Total 100 patients were taken. All the selected patients were interviewed in detail by using ICD-10. Analysis was done according to the Statistical Package for Social Science (SPSS) for windows version 25. Results: This study shows obsessive compulsive disorder is more common in young to middle age (21 to 40 years) and mean age of onset of illness was 28.31±10.21 years. Maximum (57%) were female and 43% were male. Depressive disorder, mixed anxiety and depressive disorder were most common psychiatric comorbidity (63% and 22%) in patient with OCD followed by panic disorder in 7% patients, social phobia in 5% patients, generalized anxiety disorder in 5% patients, substance abuse in 5% patients, schizophrenia in 5% patients, bipolar affective disorder in 2% patients and tic disorder in 1% patients. Conclusion: This study demonstrates a high prevalence of psychiatric comorbidities in individuals diagnosed with OCD. The most prevalent co-occurring disorders are depressive disorder & mixed anxiety and depressive disorder. KYAMC Journal Volume: 14, No: 04, January 2024: 206-209.